Correlation Between Illness Perception and Self-Management Among People With Diabetes Mellitus - Triastuti, Lidwina; Sinaga, Friska; Ari, Elizabeth (Griya Eka Sejahtera, 2025)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease with a rising global prevalence. Successful diabetes management heavily relies on patients’ engagement in self-management behaviors, which are significantly influenced by their illness perception. This study aimed to examine the correlation between illness perception and diabetes self-management among elderly individuals with type 2 diabetes.Methods: A quantitative, cross-sectional study was conducted involving 120 elderly participants with diabetes mellitus selected through purposive sampling from three community health centers. Data were collected using the Brief Illness Perception Questionnaire (Brief IPQ) and the Diabetes Self-Management Questionnaire (DSMQ). Pearson Product Moment analysis was employed to examine the correlation between the two variables.Results: The mean illness perception score was 48.72 (SD 15,75), while the mean self-management score was 78.75 (SD 11,35). A significant positive correlation was found between illness perception and self-management (p < 0.001, r = 0.568).Conclusion: Individuals with a higher perception of their illness demonstrate better self-management behaviors. Health education strategies should focus on improving illness perceptions to enhance diabetes self-management.